2006
DOI: 10.1002/art.21991
|View full text |Cite
|
Sign up to set email alerts
|

Differences in disease outcomes between medicaid and privately insured children: Possible health disparities in juvenile rheumatoid arthritis

Abstract: Objective. To determine the relationship between health insurance status and disease outcome in children with juvenile rheumatoid arthritis (JRA). Methods. JRA patients followed at a tertiary pediatric rheumatology center were assessed for the number of active joints and number of joints with limited range of motion. Disease activity, patient well-being, and pain were measured. Disability was assessed by the Childhood Health Assessment Questionnaire, health-related quality of life by the Pediatric Quality of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…Parents from a low‐SES background also reported that their child with JIA had been limited in their schoolwork or activities with friends due to emotional difficulties, had problems with their behavior and limited family activities, or had caused tension in the family. Part of these findings is similar to those found in previous studies defining SES at an individual level, such as insurance information 17, education level of parents 18, 19, 28, living in a Canadian reserve 29, and distance to health care centers 19. In this study we used area deprivation level data, which conceptually might be slightly different.…”
Section: Discussionsupporting
confidence: 81%
“…Parents from a low‐SES background also reported that their child with JIA had been limited in their schoolwork or activities with friends due to emotional difficulties, had problems with their behavior and limited family activities, or had caused tension in the family. Part of these findings is similar to those found in previous studies defining SES at an individual level, such as insurance information 17, education level of parents 18, 19, 28, living in a Canadian reserve 29, and distance to health care centers 19. In this study we used area deprivation level data, which conceptually might be slightly different.…”
Section: Discussionsupporting
confidence: 81%
“…Only a limited number of QOL studies have been conducted with children, with much of the research focusing on the areas of pediatric oncology (Eiser, Eiser, & Stride, 2005;Odame et al, 2006;Russell, Hudson, Long, & Phipps, 2006) and debilitating chronic illnesses, such as rheumatoid arthritis (Brunner et al, 2006;Riddle et al, 2006;Sawyer et al, 2005) and cystic fibrosis (Janse, Sinnema, Uiterwaal, Kimpen, & Gemke, 2004;Koscik et al, 2005;Thomas, Mitchell, O'Rourke, & Wainwright, 2006).…”
Section: Quality Of Life and Childrenmentioning
confidence: 99%
“…The paucity of appropriately trained pediatric rheumatologists and multidisciplinary teams 24 is likely to contribute to inequity in delivery of appropriate care, and increased recruitment to the specialty is needed. Access to appropriate care may be limited by healthcare costs such as in the USA, where children with JIA covered by basic healthcare insurance are less likely to have eye screening 25 . Biological agents are not available in many parts of the world, and may be subject to "rationing" based on cost-effectiveness (www.nice.org.uk), and availability may be geographically dependent on local health budgets.…”
Section: Healthcare Provisionmentioning
confidence: 99%